2021
DOI: 10.1088/1755-1315/889/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glass fiber and recycled aggregates on Geopolymer concrete

Abstract: This study presents the effect of glass fiber and recycled aggregates on the strength properties of Geopolymer Concrete (GPC). The recycled aggregates were incorporated as a partial substitute for the natural coarse aggregates in the geopolymer concrete at 50%, 80%, and 100% by weight, and the results were compared to natural coarse aggregate. Class F fly ash is utilized as the source material for the production of Geopolymer and brought in from local sources. The effect of glass fiber (alkali resistant) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In 1923, the French Paul Dhé received a US patent for his idea to extrude fibers from basalt [155]. From the 1960s, just after World War II, basalt fibers were chosen to be the best material for military research by the Soviet Union, Europe, and the United States due to their extensive use in aeronautical and defense applications [144,146]. In 1995, the fiber production technology was declassified and commenced civilian research [155].…”
Section: Basalt Fibermentioning
confidence: 99%
“…In 1923, the French Paul Dhé received a US patent for his idea to extrude fibers from basalt [155]. From the 1960s, just after World War II, basalt fibers were chosen to be the best material for military research by the Soviet Union, Europe, and the United States due to their extensive use in aeronautical and defense applications [144,146]. In 1995, the fiber production technology was declassified and commenced civilian research [155].…”
Section: Basalt Fibermentioning
confidence: 99%
“…If it is required to add superplasticiser, it can be added at the final stage (Wang et al ., 2020; Waqas et al ., 2021). However, superplasticiser was added to the binding materials, and then aggregates were added and mixed in another study (Mehta and Bhandari, 2021).…”
Section: Rca Treatmentmentioning
confidence: 99%
“…Various types of fibre, such as alkali resistance glass fibre (Mehta and Bhandari, 2021), Polyvinyl alcohol fibre (Sahin et al ., 2021b), steel fibre (Xu et al ., 2021), carbon fibres (Nuaklong et al ., 2021) and BFs (Şahin et al ., 2021a) improve the mechanical properties of the RCA-based concrete. However, the content of the fibre and the length of the fibre influence the concrete's properties.…”
Section: Rca Treatmentmentioning
confidence: 99%
“…Most used fibers to improve the strength properties of concrete are cotton fiber, carbon fiber, glass fiber and basalt fiber. The study conducted by Mehta and Bhandari [11], Blazy et al [12] investigated the effects of adding glass fibers on the mechanical properties of concrete. The study showed that the addition of glass fibers (1 % to 2.5 %) in geopolymer concrete increased the flexural strength of the specimen by 20 % compared to a specimen without glass fibers.…”
Section: Introductionmentioning
confidence: 99%